Preparation method of biodegradable polyvinyl alcohol resin packaging material

By adding modified chitosan, deoxidizer and modified microcrystalline cellulose, combined with twin screw extrusion technology, biodegradable polyvinyl alcohol resin packaging materials were prepared, which solved the problem of insufficient oxygen barrier performance and improved the Antibacterial and mechanical properties extend the shelf life of the product and promote the degradation of the material.

CN119264589AInactive Publication Date: 2025-01-07SUZHOU ZIJIN PLASTIC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411807333.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the use of existing polyvinyl alcohol films, the oxygen barrier performance is insufficient, resulting in the oxidation and deterioration of fruits and vegetables during the shelf life, and the antibacterial and anti-mold performance needs to be further improved.

Method used

By adding modified chitosan, deoxidizer and modified microcrystalline cellulose, combined with twin screw extrusion technology, a biodegradable polyvinyl alcohol resin packaging material is prepared to enhance the compatibility and mechanical properties of the material. and oxygen barrier properties promote the degradation process of the material and inhibit microbial growth under low oxygen environment.

Benefits of technology

It significantly improves the oxygen barrier properties and antibacterial properties of packaging materials, extends the shelf life of the product, maintains the quality and safety of the product, and enhances the mechanical properties and degradation properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264589A_ABST
    Figure CN119264589A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a biodegradable polyvinyl alcohol resin packaging material, and relates to the technical field of packaging materials, and the preparation method comprises the following preparation steps: step 1, adding 100-150g of polyvinyl alcohol into 500-1000g of deionized water, heating to 60-70 DEG C, and stirring for 10-30 minutes; 2, under the stirring condition, 2.5 g to 6 g of modified chitosan, 1.5 g to 2.5 g of a deoxidizing agent, 5 g to 8 g of nanofiller and 2 g to 6 g of modified microcrystalline cellulose are sequentially added, and the materials are mixed to be uniform; and step 3, adding the mixture into a double-screw extruder, melting, kneading and extruding to obtain the polyvinyl alcohol resin packaging material. According to the preparation method of the biodegradable polyvinyl alcohol resin packaging material, chitosan is modified, so that the chitosan is better dispersed in a resin matrix and prevented from being agglomerated, and the performance of the material is more uniform; the reaction activity on a molecular chain of the modified chitosan is enhanced, the interaction between the modified chitosan and the polyvinyl alcohol resin is enhanced, and the compatibility and mechanical properties of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, in particular to a method for preparing a biodegradable polyvinyl alcohol resin packaging material. Background Art

[0002] Polyvinyl alcohol is a water-soluble polymer obtained by alkali-catalyzed alcoholysis of polyvinyl acetate. As a polyhydroxyl strong polar water-soluble polymer, it has excellent comprehensive properties. For example, its mechanical properties and heat resistance are better than those of polyolefins and are comparable to those of engineering plastics. It is widely used in food packaging, industrial product packaging, daily chemical product packaging and other industries.

[0003] A Chinese patent with publication number CN108794954A discloses a polyvinyl alcohol film for fruit and vegetable packaging. The raw materials thereof include, by weight: 100 parts of polyvinyl alcohol, 10-25 parts of starch, 5-13 parts of gelatin, 2-4.8 parts of montmorillonite, 1-3 parts of activated carbon, 0.5-2 parts of zeolite, 3-5.6 parts of modified alumina, 0.5-2 parts of nano-silicon dioxide, 0.3-2 parts of chitosan quaternary ammonium salt, 2-8 parts of plant extract, 1-5 parts of spirulina, 0.01-0.09 parts of antioxidant, 2-8 parts of loofah, 0.3-0.8 parts of plant essential oil, 0.2-0.85 parts of glutamine transaminase, and 0.01-0.1 parts of antimicrobial peptide. The polyvinyl alcohol film for fruit and vegetable packaging proposed in the invention has excellent antibacterial properties, high strength, low moisture permeability, excellent heat resistance and weather resistance, and is used in fruit and vegetable preservation. It has good antibacterial and mildew resistance and can extend the shelf life of fruits and vegetables. However, the packaging material prepared by the above-mentioned prior art solution has a barrier property against oxygen during use, so the present invention provides a method for preparing a biodegradable polyvinyl alcohol resin packaging material to solve the above problem. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention provides a method for preparing a biodegradable polyvinyl alcohol resin packaging material, which solves the problems mentioned in the above background technology.

[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a biodegradable polyvinyl alcohol resin packaging material, comprising the following preparation steps: Step 1: Add 100-150g of polyvinyl alcohol to 500-1000g of deionized water, heat to 60-70°C, and stir for 10-30min; Step 2: Under stirring conditions, add 2.5-6 g of modified chitosan, 1.5-2.5 g of deoxidizer, 5-8 g of nanofiller and 2-6 g of modified microcrystalline cellulose in sequence and mix well; Step 3, adding the mixture into a twin-screw extruder, melting, kneading and extruding to obtain a polyvinyl alcohol resin packaging material; Wherein, the extrusion temperature of the twin-screw extruder is 160-240°C, and the screw speed is 350-400r / min.

[0006] Preferably, the preparation method of the modified chitosan is: (1) Pour 2.5-4 g of chitosan into 100-110 mL of isopropanol, heat to 80-85 °C, and stir to dissolve for 5-6 hours; (2) Add 1% sodium hydroxide solution dropwise to adjust the pH value of the solution to 8-9 to obtain solution A; (3) Pour 12.5-16 g of 2,3-epoxypropyltrimethylammonium chloride into 20-22 mL of deionized water, wait for it to completely dissolve, then pour it into solution A, heat it to 75-85°C, and react for 20-24 hours; (4) After the reaction is completed, the solution is dialyzed for 36-48 hours, and then filtered and freeze-dried in sequence to obtain modified chitosan.

[0007] Preferably, the preparation method of the deoxidizer is: 1) Heat 10-15mL of 1mol / L sodium chloride solution in a water bath to 25-28°C, add 5-8g of iron powder, ultrasonically treat for 10-15min, and then dry in a drying oven at 45-55°C for 45-60min; 2) Place 0.4-0.6g of nano activated carbon in a drying oven at 45-50℃ and dry for 45-60min; 3) Evenly mix the treated iron powder and nano-activated carbon, and then add 12-15mL of 0.1mol / L cuprous sulfate to obtain a deoxidizer.

[0008] Preferably, the preparation method of the nanofiller is: Pour 2-4g of polylactic acid and 0.1-0.3g of KH550 into 30-38mL of dichloromethane, add stannous octoate as a catalyst, heat to 30-35°C, and react for 1.5-2h; then add 0.2-0.5mL of deionized water and react for 0.5-0.8h; finally, add 0.1-0.2g of tetraethyl orthosilicate and hydrochloric acid as a catalyst and react for 3.5-4h to obtain a nanofiller.

[0009] Preferably, the preparation method of the modified microcrystalline cellulose is: ① Pour 50-60 mL of Tris-HCl buffer into 0.5-3 g of microcrystalline cellulose and perform ultrasonic dispersion for 10-20 min; ② Add 0.1-0.3g of dopamine hydrochloride, stir until it dissolves, and irradiate with ultraviolet light for 1.5-2h; ③ After the reaction is completed, the product is washed with ionized water for 2-4 times, and then placed in a drying oven at 55-65°C for drying to obtain modified microcrystalline cellulose.

[0010] Preferably, in said ①, the concentration of Tris-HCl buffer is 40 mol / L, and the pH value is 8.3-8.7.

[0011] Preferably, the preparation method of the microcrystalline cellulose is: Ⅰ. Place 6-10g of cotton fabric fiber in 75-100mL of sodium hypochlorite solution and soak it at room temperature for 0.3-0.5h, then wash, dry and grind it in sequence; Ⅱ. Place it in a 10% sodium hydroxide solution, boil it for 1.5-2h under stirring, then wash it with deionized water until it becomes neutral and dry it; III. Place in 130-150 mL of hydrochloric acid solution, heat to 70-80°C, and stir to react for 2-2.2 hours; IV. Wash by centrifugation at a speed of 6000-8000 r / min until neutral, dry in a drying oven at 55-65°C, and grind to obtain microcrystalline cellulose.

[0012] Preferably, in said Ⅰ, the concentration of the sodium hypochlorite solution is 6%; the length of the cotton fabric fibers after grinding is 2-5 mm; and in said Ⅲ, the concentration of the hydrochloric acid solution is 3 mol / L. Beneficial Effects

[0013] The present invention provides a method for preparing a biodegradable polyvinyl alcohol resin packaging material. Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the biodegradable polyvinyl alcohol resin packaging material comprises the following steps: modifying chitosan so that chitosan is better dispersed in the resin matrix to prevent it from agglomerating, thereby making the material performance more uniform; the reaction activity of the modified chitosan molecular chain is enhanced, and the interaction between the chitosan and the polyvinyl alcohol resin is enhanced, thereby improving the compatibility and mechanical properties of the material; and the amino groups and other active groups on the modified chitosan will attract enzymes produced by microorganisms, thereby increasing the contact opportunities between the enzymes and the packaging material, thereby accelerating the degradation process of the polyvinyl alcohol resin packaging material; at the same time, the modified chitosan has a positive charge and can destroy the cell structure of microorganisms, thereby inhibiting the growth and reproduction of microorganisms and improving the antibacterial properties of the packaging material.

[0014] (2) The preparation method of the biodegradable polyvinyl alcohol resin packaging material can effectively reduce the oxygen content inside the packaging by adding a deoxidizer, thereby delaying the oxidation and deterioration process of the product and extending the shelf life; at the same time, the reduction in oxygen content can also inhibit the growth and reproduction of aerobic microorganisms. In a low-oxygen environment, the growth of aerobic microorganisms is restricted, thereby reducing the risk of product contamination by microorganisms and maintaining the quality and safety of the product.

[0015] (3) The preparation method of the biodegradable polyvinyl alcohol resin packaging material comprises the following steps: modifying microcrystalline cellulose to enhance the interfacial bonding ability between microcrystalline cellulose and the resin matrix, so that when the material is subjected to external force, stress can be effectively transmitted, thereby improving the mechanical properties of the packaging material; and the modified microcrystalline cellulose is more evenly dispersed in the resin matrix, filling the voids in the resin matrix, reducing the permeability of gas and water vapor, thereby improving the barrier properties of the packaging material and better maintaining the quality of the product; since microcrystalline cellulose itself is a natural degradable material, the modified microcrystalline cellulose can better fuse with the polyvinyl alcohol resin, forming a loose structure inside the material that is conducive to degradation, increasing the contact area between the material and the external environment, and improving the degradation performance; at the same time, the modified components such as the polydopamine coating on its surface may undergo their own degradation reaction under certain environmental conditions, thereby driving the degradation process of the entire packaging material.

[0016] In this technical solution, modified chitosan and modified microcrystalline cellulose improve the oxygen barrier properties of packaging materials and reduce oxygen penetration. At the same time, the deoxidizer can actively consume the oxygen inside the package to create a low-oxygen environment for the products in the package, effectively inhibiting the oxidation of fats and oils in food, the oxidation of pharmaceutical ingredients, and other processes, and maintaining the quality and flavor of the products; at the same time, they work together in the packaging material to construct a stable three-dimensional network structure, which significantly improves the mechanical properties of the packaging material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a comparison chart of the degradation performance test of the polyvinyl alcohol resin packaging material of the present invention. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0019] A method for preparing a biodegradable polyvinyl alcohol resin packaging material comprises the following preparation steps: Step 1: Add 100 g of polyvinyl alcohol to 1000 g of deionized water, heat to 60°C, and stir for 10 minutes; Step 2: Under stirring conditions, add 6 g of modified chitosan, 2.5 g of deoxidizer, 8 g of nanofiller and 6 g of modified microcrystalline cellulose in sequence and mix well; The preparation method of modified chitosan is as follows: pour 2.5 g of chitosan into 100 mL of isopropanol, heat to 80°C, and stir to dissolve for 5 hours; add a 1% sodium hydroxide solution by mass, adjust the pH value of the solution to 8, and obtain solution A; pour 12.5 g of 2,3-epoxypropyltrimethylammonium chloride into 20 mL of deionized water, and after it is completely dissolved, pour it into solution A, heat to 75°C, and react for 20 hours; after the reaction is completed, dialyze the solution for 36 hours, and then filter and freeze-dry in sequence to obtain modified chitosan; The preparation method of the deoxidizer is as follows: after heating 10 mL of a sodium chloride solution with a concentration of 1 mol / L to 25° C. in a water bath, pour in 5 g of iron powder, perform ultrasonic treatment for 10 min, and then place in a drying oven at 45° C. to dry for 45 min; place 0.4 g of nano-activated carbon in a drying oven at 45° C. to dry for 45 min; mix the treated iron powder and nano-activated carbon evenly, and then add 12 mL of cuprous sulfate with a concentration of 0.1 mol / L to obtain the deoxidizer; The preparation method of the nanofiller is as follows: 2 g of polylactic acid and 0.1 g of KH550 are poured into 30 mL of dichloromethane, and stannous octoate is added as a catalyst, the temperature is raised to 30°C, and the reaction is carried out for 1.5 hours; then 0.2 mL of deionized water is added, and the reaction is carried out for 0.5 hours; finally, 0.1 g of tetraethyl orthosilicate is added, and hydrochloric acid is added as a catalyst, and the reaction is carried out for 3.5 hours to obtain the nanofiller; The preparation method of modified microcrystalline cellulose is: (1) 6 g of cotton fabric fiber is placed in 75 mL of a 6% sodium hypochlorite solution, and soaked at room temperature for 0.3 h, and then washed, dried, and ground to a length of 2 mm; then placed in a 10% sodium hydroxide solution, boiled for 1.5 h under stirring, and then washed with deionized water until neutral and dried; placed in 130 mL of a 3 mol / L hydrochloric acid solution, heated to 70°C, and stirred for reaction for 2 h; centrifuged at 6000 r / min to neutral, and then placed in a drying oven at 55°C to dry and grind to obtain microcrystalline cellulose; (2) Pour 0.5 g of microcrystalline cellulose into 50 mL of Tris-HCl buffer with a concentration of 40 mol / L and a pH value of 8.3, and perform ultrasonic dispersion treatment for 10 min; add 0.1 g of dopamine hydrochloride, stir until it is dissolved, and irradiate with ultraviolet light for 1.5 h; after the reaction is completed, wash the product twice with deionized water, and then dry it in a drying oven at 55°C to obtain modified microcrystalline cellulose; Step 3: Add to a twin-screw extruder, set the extrusion temperature at 160°C and the screw speed at 350 r / min, and obtain the polyvinyl alcohol resin packaging material through melting, kneading and extrusion. Example 2

[0020] A method for preparing a biodegradable polyvinyl alcohol resin packaging material comprises the following preparation steps: Step 1: Add 125 g of polyvinyl alcohol to 750 g of deionized water, heat to 65°C, and stir for 20 min; Step 2: Under stirring conditions, add 4.5 g of modified chitosan, 2 g of deoxidizer, 6 g of nanofiller and 4 g of modified microcrystalline cellulose in sequence and mix well; The preparation method of modified chitosan is as follows: pour 3g of chitosan into 105mL of isopropanol, heat to 82°C, and stir to dissolve for 5.5h; add 1% sodium hydroxide solution by mass, adjust the pH value of the solution to 8.5, and obtain solution A; pour 14g of 2,3-epoxypropyltrimethylammonium chloride into 21mL of deionized water, and after it is completely dissolved, pour it into solution A, heat to 80°C, and react for 22h; after the reaction is completed, dialyze the solution for 42h, and then filter and freeze-dry in sequence to obtain modified chitosan; The preparation method of the deoxidizer is as follows: 12 mL of a sodium chloride solution with a concentration of 1 mol / L is heated to 26° C. in a water bath, 7 g of iron powder is poured in, ultrasonic treatment is performed for 12 min, and then the solution is placed in a drying oven at 505° C. for 50 min; 0.5 g of nano-activated carbon is placed in a drying oven at 48° C. for 50 min; the treated iron powder and the nano-activated carbon are evenly mixed, and 13 mL of cuprous sulfate with a concentration of 0.1 mol / L is added to obtain the deoxidizer; The preparation method of the nanofiller is as follows: 3 g of polylactic acid and 0.2 g of KH550 are poured into 34 mL of dichloromethane, and stannous octoate is added as a catalyst, the temperature is raised to 32° C., and the reaction is carried out for 1.8 hours; then 0.3 mL of deionized water is added, and the reaction is carried out for 0.6 hours; finally, 0.2 g of tetraethyl orthosilicate is added, and hydrochloric acid is added as a catalyst, and the reaction is carried out for 3.8 hours to obtain the nanofiller; The preparation method of modified microcrystalline cellulose is: (1) 8 g of cotton fabric fiber is placed in 85 mL of a 6% sodium hypochlorite solution, and soaked at room temperature for 0.4 h, and then washed, dried, and ground to a length of 3 mm; then placed in a 10% sodium hydroxide solution, boiled for 1.8 h under stirring, and then washed with deionized water until neutral and dried; placed in 140 mL of a 3 mol / L hydrochloric acid solution, heated to 75°C, and stirred for 2.1 h; centrifuged at 7000 r / min to neutral, and then placed in a drying oven at 60°C to dry and grind to obtain microcrystalline cellulose; (2) Pour 2 g of microcrystalline cellulose into 55 mL of Tris-HCl buffer with a concentration of 40 mol / L and a pH value of 8.5, and perform ultrasonic dispersion treatment for 15 min; add 0.2 g of dopamine hydrochloride, stir until it is dissolved, and irradiate with ultraviolet light for 1.8 h; after the reaction is completed, wash the product with deionized water for 3 times, and then dry it in a drying oven at 60°C to obtain modified microcrystalline cellulose; Step 3: Add to a twin-screw extruder, set the extrusion temperature at 200°C, and the screw speed at 370 r / min, and obtain the polyvinyl alcohol resin packaging material through melting, kneading, and extrusion. Example 3

[0021] A method for preparing a biodegradable polyvinyl alcohol resin packaging material comprises the following preparation steps: Step 1: Add 150 g of polyvinyl alcohol to 500 g of deionized water, heat to 70°C, and stir for 30 minutes; Step 2: Under stirring conditions, add 2.5 g of modified chitosan, 1.5 g of deoxidizer, 5 g of nanofiller and 2 g of modified microcrystalline cellulose in sequence and mix well; The preparation method of modified chitosan is as follows: pour 4 g of chitosan into 110 mL of isopropanol, heat to 85°C, and stir to dissolve for 6 hours; add a 1% sodium hydroxide solution by mass, adjust the pH value of the solution to 9, and obtain solution A; pour 16 g of 2,3-epoxypropyltrimethylammonium chloride into 22 mL of deionized water, and after it is completely dissolved, pour it into solution A, heat to 85°C, and react for 24 hours; after the reaction is completed, dialyze the solution for 48 hours, and then filter and freeze-dry in sequence to obtain modified chitosan; The preparation method of the deoxidizer is as follows: 15 mL of a sodium chloride solution with a concentration of 1 mol / L is heated to 28° C. in a water bath, 8 g of iron powder is poured in, ultrasonically treated for 15 min, and then placed in a drying oven at 55° C. for 60 min; 0.6 g of nano-activated carbon is placed in a drying oven at 50° C. for 60 min; the treated iron powder and nano-activated carbon are evenly mixed, and 15 mL of cuprous sulfate with a concentration of 0.1 mol / L is added to obtain the deoxidizer; The preparation method of the nanofiller is as follows: 4 g of polylactic acid and 0.3 g of KH550 are poured into 38 mL of dichloromethane, and stannous octoate is added as a catalyst, the temperature is raised to 35° C., and the reaction is carried out for 2 hours; then 0.5 mL of deionized water is added, and the reaction is carried out for 0.8 hours; finally, 0.2 g of tetraethyl orthosilicate is added, and hydrochloric acid is added as a catalyst, and the reaction is carried out for 4 hours to obtain the nanofiller; The preparation method of modified microcrystalline cellulose is: (1) 10 g of cotton fabric fiber is placed in 100 mL of a 6% sodium hypochlorite solution, and soaked at room temperature for 0.5 h, and then washed, dried, and ground to a length of 5 mm; then placed in a 10% sodium hydroxide solution, boiled for 2 h under stirring, and then washed with deionized water until neutral and dried; placed in 150 mL of a 3 mol / L hydrochloric acid solution, heated to 80°C, and stirred for 2.2 h; centrifuged at 8000 r / min to neutral, and then placed in a drying oven at 65°C to dry and grind to obtain microcrystalline cellulose; (2) 3 g of microcrystalline cellulose was poured into 60 mL of Tris-HCl buffer with a concentration of 40 mol / L and a pH value of 8.7, and subjected to ultrasonic dispersion for 20 min; 0.3 g of dopamine hydrochloride was added, stirred until dissolved, and then irradiated with ultraviolet light for 2 h; after the reaction was completed, the product was washed with deionized water for 4 times, and then dried in a drying oven at 65°C to obtain modified microcrystalline cellulose; Step 3: Add to a twin-screw extruder, set the extrusion temperature at 240°C, and the screw speed at 400 r / min, and obtain the polyvinyl alcohol resin packaging material through melting, kneading, and extrusion.

[0022] Comparative Example 1 Compared with Example 1, the difference is that the modified chitosan in Example 1 is replaced by chitosan.

[0023] Comparative Example 2 Compared with Example 1, the difference is that the deoxidizer in Example 1 is deleted.

[0024] Comparative Example 3 Compared with Example 1, the difference lies in that the modified microcrystalline cellulose in Example 1 is replaced by microcrystalline cellulose.

[0025] Barrier performance test: The water vapor permeability of the sample was tested using a water vapor permeability tester; the gas permeability of the sample was measured according to GB / T1038.1-2022; the results are shown in Table 1.

[0026] Table 1

[0027] Tensile strength test: The test was conducted according to GB / T1040.1-2006; the results are shown in Table 2.

[0028] Antibacterial performance test: The antibacterial performance of packaging materials against Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus) was tested by using the film contact antibacterial method. The bacterial solution (5x10 4 / mL), so that it forms a film on the sample, observe the action time for 12h and 24h, wash the colonies with PBS solution, transfer them to a culture dish, add nutrient agar medium (NA), and culture at 37℃ for 24h. The number of bacteria is detected by the viable bacteria counting method: antibacterial rate (%) = (number of bacteria recovered from the control sample - number of bacteria recovered from the test sample) / number of bacteria recovered from the control sample × 100%; the results are shown in Table 2.

[0029] Table 2

[0030] Degradation performance test: Select Penicillium as the degradation colony, put the sample into the culture medium in the culture dish, inoculate the Penicillium colony, completely seal the culture dish, and culture it at 28°C and 75% relative humidity, and observe the culture conditions.

[0031] like Figure 1 As shown, compared with Comparative Examples 1-3, the mass loss of the samples in Examples 1-3 was about 5% within 12 days, and the degradation effect was good.

[0032] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0033] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0034] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a biodegradable polyvinyl alcohol resin packaging material, characterized in that: The method comprises the following preparation steps: Step 1: Add 100-150g of polyvinyl alcohol to 500-1000g of deionized water, heat to 60-70°C, and stir for 10-30min; Step 2: Under stirring conditions, add 2.5-6 g of modified chitosan, 1.5-2.5 g of deoxidizer, 5-8 g of nanofiller and 2-6 g of modified microcrystalline cellulose in sequence and mix well; Step 3, adding the mixture into a twin-screw extruder, melting, kneading and extruding to obtain a polyvinyl alcohol resin packaging material; Wherein, the extrusion temperature of the twin-screw extruder is 160-240°C, and the screw speed is 350-400r / min.

2. The method for preparing a biodegradable polyvinyl alcohol resin packaging material according to claim 1, characterized in that: The preparation method of the modified chitosan is: (1) Pour 2.5-4 g of chitosan into 100-110 mL of isopropanol, heat to 80-85 °C, and stir to dissolve for 5-6 hours; (2) Add 1% sodium hydroxide solution dropwise to adjust the pH value of the solution to 8-9 to obtain solution A; (3) Pour 12.5-16 g of 2,3-epoxypropyltrimethylammonium chloride into 20-22 mL of deionized water, wait for it to completely dissolve, then pour it into solution A, heat it to 75-85°C, and react for 20-24 hours; (4) After the reaction is completed, the solution is dialyzed for 36-48 hours, and then filtered and freeze-dried in sequence to obtain modified chitosan.

3. The method for preparing a biodegradable polyvinyl alcohol resin packaging material according to claim 1, characterized in that: The preparation method of the deoxidizer is: 1) Heat 10-15mL of 1mol / L sodium chloride solution in a water bath to 25-28°C, add 5-8g of iron powder, ultrasonically treat for 10-15min, and then dry in a drying oven at 45-55°C for 45-60min; 2) Place 0.4-0.6g of nano activated carbon in a drying oven at 45-50℃ and dry for 45-60min; 3) Evenly mix the treated iron powder and nano-activated carbon, and then add 12-15mL of cuprous sulfate with a concentration of 0.1mol / L to obtain the deoxidizer.

4. The method for preparing a biodegradable polyvinyl alcohol resin packaging material according to claim 1, characterized in that: The preparation method of the nanofiller is: Pour 2-4g of polylactic acid and 0.1-0.3g of KH550 into 30-38mL of dichloromethane, add stannous octoate as a catalyst, heat to 30-35°C, and react for 1.5-2h; then add 0.2-0.5mL of deionized water and react for 0.5-0.8h; finally, add 0.1-0.2g of tetraethyl orthosilicate and hydrochloric acid as a catalyst and react for 3.5-4h to obtain a nanofiller.

5. The method for preparing a biodegradable polyvinyl alcohol resin packaging material according to claim 1, characterized in that: The preparation method of the modified microcrystalline cellulose is: ① Pour 50-60 mL of Tris-HCl buffer into 0.5-3 g of microcrystalline cellulose and perform ultrasonic dispersion for 10-20 min; ② Add 0.1-0.3g of dopamine hydrochloride, stir until it dissolves, and irradiate with ultraviolet light for 1.5-2h; ③ After the reaction is completed, the product is washed with ionized water for 2-4 times, and then placed in a drying oven at 55-65°C for drying to obtain modified microcrystalline cellulose.

6. The method for preparing a biodegradable polyvinyl alcohol resin packaging material according to claim 5, characterized in that: In the above ①, the concentration of Tris-HCl buffer is 40 mol / L, and the pH value is 8.3-8.

7.

7. The method for preparing a biodegradable polyvinyl alcohol resin packaging material according to claim 5, characterized in that: The preparation method of the microcrystalline cellulose is: Ⅰ. Place 6-10g of cotton fabric fiber in 75-100mL of sodium hypochlorite solution and soak it at room temperature for 0.3-0.5h, then wash, dry and grind it in sequence; Ⅱ. Place it in a 10% sodium hydroxide solution, boil it for 1.5-2h under stirring, then wash it with deionized water until it becomes neutral and dry it; III. Place in 130-150 mL of hydrochloric acid solution, heat to 70-80°C, and stir to react for 2-2.2 hours; IV. Wash by centrifugation at a speed of 6000-8000 r / min until neutral, dry in a drying oven at 55-65°C, and grind to obtain microcrystalline cellulose.

8. The method for preparing a biodegradable polyvinyl alcohol resin packaging material according to claim 7, characterized in that: In said Ⅰ, the concentration of the sodium hypochlorite solution is 6%; the length of the cotton fabric fiber after grinding is 2-5mm; in said Ⅲ, the concentration of the hydrochloric acid solution is 3mol / L.

Citation Information

Patent Citations

  • Special polyvinyl alcohol thin film for fruit and vegetable packaging

    CN108794954A

  • High-transparency breathable fresh-keeping film bag and preparation method thereof

    CN109206884A

  • Preparation method of modified bacterial cellulose membrane for periodontal tissue repair

    CN115337464A

  • PVA film filled with modified cellulose as well as preparation method and application of PVA film

    CN116253964A

  • Fruit preservative as well as preparation method and application thereof

    CN117378669A